Suscetível a Leptospira interrogans para os venenos de cobra - Ciuffa, A. Z.; Gomes, D. O.; Pires, B. C.; Resende, L. M.; Veloso, L. I.; Rodrigues, R. S.; Rodrigues, V. M.; Lima, A. M. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Nowadays bacterial resistance to antibiotics are becoming an important cause of failures in infectious diseases therapy. Snake venoms have antimicrobial activity and are being used as drugs. Their activity on Leptospira is still unknown.